1971
DOI: 10.1126/science.173.4001.1036
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone: One Polypeptide Regulates Secretion of Luteinizing and Follicle-Stimulating Hormones

Abstract: A polypeptide isolated from porcine hypothalami stimulates the release of both luteinizing hormone and follicle-stimulating hormone from the pituitaries of several species. This polypeptide has been structurally identified as (pyro)Glu-His-Trp-Ser-Tyr-Gly-Leu-Arg-Pro-Gly-NH(2) and synthesized. The natural and synthetic materials share biological properties. It appears that this peptide represents the hypothalamic hormone regulating the secretion of both luteinizing hormone and follicle-stimulating hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
243
0
24

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 709 publications
(270 citation statements)
references
References 17 publications
3
243
0
24
Order By: Relevance
“…Cells at logarithmic growth phase were harvested using 0.25% trypsin-0.02% EDTA solution for 5 min, pelleted by centrifugation at 500g for 5 min, washed once with medium and resuspended at a concentration of 1ϫ10 4 cells/ml DMEM medium. Cells of 1ϫ10 4 or 1ϫ10 5 were incubated in 24-well plate (for growth study) and 10 cm dish (for collecting cellular proteins), respectively. The cells were then incubated at 37°C for 24 hr to allow the attachment to plates.…”
Section: Growth Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells at logarithmic growth phase were harvested using 0.25% trypsin-0.02% EDTA solution for 5 min, pelleted by centrifugation at 500g for 5 min, washed once with medium and resuspended at a concentration of 1ϫ10 4 cells/ml DMEM medium. Cells of 1ϫ10 4 or 1ϫ10 5 were incubated in 24-well plate (for growth study) and 10 cm dish (for collecting cellular proteins), respectively. The cells were then incubated at 37°C for 24 hr to allow the attachment to plates.…”
Section: Growth Experimentsmentioning
confidence: 99%
“…4 Accumulated data have indicated that LHRH might also present in extra-hypothalamic tissues, such as ovary, testis, kidney and placenta. 5 Currently, more than 3,000 analogues of LHRH have been synthesized.…”
mentioning
confidence: 99%
“…Исследования в области нейроэндокрино-логии, основоположниками которой являются прежде всего Джеффри Харрис [Harris, 1948[Harris, , 1972, а также Нобелевские лауреаты Роже Гий-мен [Guillemin, Rosenberg, 1955] и Эндрю Шал-ли [Schally et al, 1971], позволили выяснить, что регуляция многих метаболических и поведен-ческих реакций осуществляется посредством эндокринных «осей» [Raisman, 1997]. В эти оси K e y w o r d s: steroid hormones; glucocorticoids; mineralocorticoids; steroidogenesis; osmoregulation; cortisol; aldosterone.…”
Section: особенности биосинтеза стероидных гормонов у костистых рыбunclassified
“…Была доказана безопасность агонистов ЛГРГ и эффективность, сопоставимая с эффектом эстрогенотерапии. Эти исследования определили концепцию андрогенной депривации для современ-ной AДТ [8][9][10][11][12][13].…”
unclassified